39-Week Nulliparous Inductions Are Not Elective. Issue 1 (24th March 2021) - Ghartey, J.; Macones, G.A.
Abstract : ( Am J Obstet Gynecol . 2020;222:519–520) The ARRIVE trial, whose findings were published in 2018, randomly assigned over 6000 women to either "elective" labor induction at 39 weeks (n=3062), or to expectant management (n=3044). The primary outcome, a composite of adverse perinatal outcomes, showed no difference between the 2 groups. In fact, women undergoing induction of labor were significantly less likely to experience hypertensive disorders of pregnancy, or to require cesarean delivery. However, despite these and similar findings in other studies, labor induction for low-risk women has not been widely adopted.